Posisi Strategi Bersaing Bisnis Pembenihan Udang Vaname Dengan Pendekatan Competitive Profil Matrix (Studi Pada PT. Semar Emas Situbondo, Jawa Timur) - Remiasa, Marcus; Sugiharto, Terry (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2019)
The business competition of vannamei shrimp seed has strongly expanded by the increasing of Indonesian shrimp export. The businessman competes in preparing vannamei shrimp seed for Indonesian fisherman. The ability of competition has influenced in company competitive strategy. This research aimed to identify the position of competitive strategy and to know the strong and low point of critical success factor (CSF) in the business of vannamei shrimp seed. This research used descriptive qulaititative research by using phenomenology. The technic of data collecting used interview and direct observation to the research subject. The research result by using Competitive Profile Matrix (CPM) showed that the position of competitive strategy in PT Semar Emas is not strong enough yet as its competitor, PT Dewa Ndaru. The competition ability of PT Semar Emas can be showed in critical success factor (CSF) with the low point in the old company management, the traditional marketing management, the government policy and unstable economic condition. The strong point is in the product location of vannamei shrimp seed and the quality of humanresource.